Evaluation of the Activity of Essential Oil and Hydrosol from Eucalyptus Camaldulensis Against Some Bacterial Species - Khalaf, Zainab Zamel; Zahra, Lamiaa Abdul (Iraqi Journal of Science, 2020)
Nowadays, the use of medicinal plants is being practiced at a wide range as a result of antibiotics resistant for the vast majority of microorganisms. Eucalyptus camaldulensis essential oil and hydrosol were used in this study against planktonic forms and biofilms of some species of Gram negative and Gram positive bacteria. The antibacterial and antibiofilm activities of this plant were detected using the microtiter plate and MIC approaches. The results proposed that the oil and hydrosol preparations have antibacterial activities against planktonic cells in different concentrations depending on the type of isolate. For antibiofilm activity, the results showed that E. camaldulensis oil was highly effective against bacterial biofilms of different bacterial species in comparison with the hydrosol. In conclusions, the studied plant can be used as an alternative treatment against bacterial biofilms that cause chronic infections for humans and animals.